DUKUNGAN KELUARGA MENINGKATKAN HEALTH SEEKING BEHAVIOUR PADA PENDERITA DIABETES MELITUS - Munir, Nur Wahyuni; Sididi, Mansur; Ramdhani, Salsabila Nuru; Sainul, Salmila (Journal of Borneo Holistic Health, 2025)
Every individual tries to seek treatment for themselves in order to maintain or improve their health status.  The aim of this research is to determine the relationship between family support and health seeking behavior in DM sufferers in the Paccerakkang Makassar Health Center Work Area. This research uses a correlation analytical method with a cross sectional study design. Samples were taken using purposive sampling from 80 DM sufferers. The research instrument uses a valid and reliable questionnaire sheet. The data analysis used was the Chi-square test with a significance level of 0.05. The results of the research showed that family support was in the good category as many as 52 people (65%) and not so good as many as 28 people (35%), health seeking behavior was good and not so good for 40 people (50%), and there was a relationship between family support and health seeking behavior in DM sufferers (p value = 0.035). The conclusion from this research is that the better the family support, the better the health seeking behavior in DM sufferers.